2016
DOI: 10.3390/s16081272
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Ochrobactrum anthropi YC152 in a Microbial Fuel Cell as an Early Warning Device for Hexavalent Chromium Determination

Abstract: Fast hexavalent chromium (Cr(VI)) determination is important for environmental risk and health-related considerations. We used a microbial fuel cell-based biosensor inoculated with a facultatively anaerobic, Cr(VI)-reducing, and exoelectrogenic Ochrobactrum anthropi YC152 to determine the Cr(VI) concentration in water. The results indicated that O. anthropi YC152 exhibited high adaptability to pH, temperature, salinity, and water quality under anaerobic conditions. The stable performance of the microbial fuel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…Nevertheless, the proposed MFCs showed limitations in Cr(VI) detection at higher pH conditions. Which was overcame later [ 120 , 121 ]. Guey-Horng Wang et al [ 120 ] suggested the use of an MFC based biosensor inoculated with a facultatively anaerobic, a Cr(VI)-reducing Ochrobactrum anthropi YC152 for Cr(VI) measurements in water.…”
Section: Electrochemical Biosensors For Hexavalent Chromium Determmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the proposed MFCs showed limitations in Cr(VI) detection at higher pH conditions. Which was overcame later [ 120 , 121 ]. Guey-Horng Wang et al [ 120 ] suggested the use of an MFC based biosensor inoculated with a facultatively anaerobic, a Cr(VI)-reducing Ochrobactrum anthropi YC152 for Cr(VI) measurements in water.…”
Section: Electrochemical Biosensors For Hexavalent Chromium Determmentioning
confidence: 99%
“…Which was overcame later [ 120 , 121 ]. Guey-Horng Wang et al [ 120 ] suggested the use of an MFC based biosensor inoculated with a facultatively anaerobic, a Cr(VI)-reducing Ochrobactrum anthropi YC152 for Cr(VI) measurements in water. The Ochrobactrum anthropi YC152 displayed high adaptability to pH (5–8), salinity, temperature and quality of water under anaerobic conditions.…”
Section: Electrochemical Biosensors For Hexavalent Chromium Determmentioning
confidence: 99%
“…An MFC‐based biosensor for the determination of Cr(VI) in water was designed by inoculating the facultatively anaerobic, Cr(VI)‐reducing exoelectrogenic bacterium Ochrobactrum anthropi YC152 into the anode compartment . This chromate‐reducing bacterium converted the organics to carbon dioxide and also Cr(VI) to Cr(III), with the generation of protons and electrons.…”
Section: Recent Developments For Cr(vi) Reduction In Mfcsmentioning
confidence: 99%
“…79 An MFC-based biosensor for the determination of Cr(VI) in water was designed by inoculating the facultatively anaerobic, Cr(VI)-reducing exoelectrogenic bacterium Ochrobactrum anthropi YC152 into the anode compartment. 80 This chromatereducing bacterium converted the organics to carbon dioxide and also Cr(VI) to Cr(III), with the generation of protons and electrons. The biosensor was based on the concept that the higher the concentration of Cr(VI) in the anode, the fewer electrons are transferred to the cathode at constant organic concentration.…”
Section: Recent Developments For Cr(vi) Reduction In Mfcsmentioning
confidence: 99%
“…In one case, the inoculum source is a compound substance such as anaerobic sludge, soil, or domestic wastewater, which provides a bacterial consortium for the anode chamber [ 29 , 30 , 31 ]. Alternatively, pure cultures have been used as anode inoculum in recent studies [ 32 , 33 , 34 ].…”
Section: The Mechanisms Governing Mfcs Used As Biosensorsmentioning
confidence: 99%